Urban heritage and cultural tourism development: a case study of Valletta's role in Malta's tourism. Issue 3 (4th May 2019) - Ebejer, John
ABSTRACT: Despite significant potential for cultural tourism, the predominant form of tourism in Malta is sun and sea. This paper evaluates Malta's potential for cultural tourism with a focus on Valletta, a fortified historic city that overlooks the Grand Harbour. Valletta's rich urban heritage and historic narrative makes it ideal for the development of a more culture-oriented tourism. The paper explores how, over more than half a century of tourism activity in Malta, culture and heritage retained a secondary role. Since the mid-nineties, Malta's tourism policy shifted with culture and heritage being given greater importance, even if the sun and sea tourism remained a priority. Public and private investment brought about changes in Valletta that made it more amenable to cultural activity and tourism. Although European Capital of Culture Valletta 2018 provides new opportunities for cultural tourism to Malta, it is unclear whether this will bring a lasting legacy for Malta's tourism. This Valletta case study shows that, for destinations with an established form of tourism, the development of cultural tourism meets with difficulties, in spite the presence of a rich urban heritage.